(3JCKjQ GdSjGSGJ GdGbJUGOjI Ydi GdMedGJ GdEYdGfjI ai GdUMa GdjhejI (B: s (3OQGSI JbhjejI NdGd YGe (B2008/ s - (3CMeO eMehO YHOGdMdje eMehOs; (3eMehO SdjeGf Yde GdOjf (B: s ((3GdbGgQI (B: s (3CMeO eMehO YHOGdMdje eMehO (B: s, 2015)
(3JJfGhd GdOQGSI GdSjGSGJ GdGbJUGOjI h JCKjQgG Ydi GdMedGJ GdEYdGfjI ai GdUMa GdjhejI (B( (3OQGSI JbhjejI NdGd YGe (B2008 ) (3HGYJHGQ gPg GdSjGSGJ eONdGJ JDKQ ai GdeeGQSI GdEYdGfjI ddMedGJ GdEYdGfjI dJaQR eLehYI ef GdeNQLGJ GdeGdjI h GdGbJUGOjI h GdafjI h GdGLJeGYjI h GdKbGajI h GdCNdGbjI GdJi JMOO WHjYI GdCOGA GdEYdGfi GdUMai eY GdCNP ai GdGYJHGQ GdYhGed GdHjFjI GdJi JTcd gPg GdSjGSGJ ShGA ef OGNd efXeGJ GdCYeGd Ch TQcGJ h hcGdGJ GdEYdGf h GdUMa h GdeDSSGJ GdUMajI (B: (3Ch ef NGQLgGs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEYdGe (B- (3bSe GdUMGaIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdMedGJ GdEYdGfjI ai GdUMas; (3GdSjGSGJ GdGbJUGOjIs; (3GdUMa GdjhejIs